2022
DOI: 10.3390/sym14010160
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Energy Forecasting Using Machine-Learning-Based Ensemble Voting Regression

Abstract: Meeting the required amount of energy between supply and demand is indispensable for energy manufacturers. Accordingly, electric industries have paid attention to short-term energy forecasting to assist their management system. This paper firstly compares multiple machine learning (ML) regressors during the training process. Five best ML algorithms, such as extra trees regressor (ETR), random forest regressor (RFR), light gradient boosting machine (LGBM), gradient boosting regressor (GBR), and K neighbors regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…LSTMs are susceptible to specific initializations of activation functions (Li [21]). Phyo et al [22] suggested the utilization of machine learning algorithms with reduced error rates that are taught to create the planned voting regressor model, which is essential for energy producers in order to meet the needed quantity of energy between consumption and supply. The classification of data set is more complex by using this model.…”
Section: Literature Surveymentioning
confidence: 99%
“…LSTMs are susceptible to specific initializations of activation functions (Li [21]). Phyo et al [22] suggested the utilization of machine learning algorithms with reduced error rates that are taught to create the planned voting regressor model, which is essential for energy producers in order to meet the needed quantity of energy between consumption and supply. The classification of data set is more complex by using this model.…”
Section: Literature Surveymentioning
confidence: 99%
“…Based on the closest distance, the most related K value is chosen to categorize the input features. The KNN algorithms rely on the voting function of the chosen ideal k value and distance [40,42,58,68,69]. The KNN techniques have been employed in various studies with a significant level of accuracy, including one where short-term energy forecasted was performed with a mean absolute percentage error (MAPE) of 4% [68] and the estimation of chlorophyll-a and suspended solids concentration in water bodies in Brazil with R 2 > 80%.…”
Section: Standalone ML Techniquesmentioning
confidence: 99%
“…Hyperparameters for the GBM include the number of iterations, the learning rate, the loss function, and the maximum depth of the single weak models. The boosting model consists of several logistic regression or decision trees built by relying on some randomly chosen trees, with its performance improved by iteratively adding new randomly chosen decision trees which help to improve the accuracy of the previous iteration model [57,68,76].…”
Section: Ensemble ML Techniquesmentioning
confidence: 99%
“…At this point, MW prediction has problems such as limited data and many parameters affecting the amount of MW, so there is a need for more powerful algorithms, such as ensemble methods based on ML algorithms, to handle these problems. However, to the best of our knowledge, no investigations have been undertaken utilizing the random forest (RF), gradient boosting machine (GBM), and adaptive boosting (AdaBoost) algorithms to predict MW amounts, nor any utilizing ensemble methods based on ML algorithms, which are considered to represent a better approach than single algorithms [25][26][27][28][29][30]. Instead of using single machine learning algorithms, this study proposed ensemble voting regression (VR) algorithms based on machine learning to obtain better predictions of MW generation in ˙Istanbul, the largest city in Turkey, utilizing official data.…”
Section: Introductionmentioning
confidence: 99%